Shape Memory-Enhanced Electrical Self-Healing of Stretchable Electrodes - Hongsheng Luo (Applied Sciences, 2018)
A novel shape memory-based self-healable stretchable electrode was explored by embedding the silver nanowires (AgNWs) network into a healable polymer matrix. Unlike the traditional shape memory-assisted self-healing, pre-stretching to the temporary shapes, which was fixed in a typical shape, memory thermo-mechanical programming significantly enhanced the thermo-triggered healing performance. The morphological as well as conduction variations during the healing process were investigated. The enhancing effect of the pre-stretching on the healing efficiency was emphasized, which was expected to attribute to the release of the pre-stored strain energy driving the closure of the scratch. The findings disclosed how to utilize the shape memory effect to improve the biomimetic properties for the stretchable electrodes, which may greatly benefit the application of the intelligent polymers in the field of multi-functional flexible electronics.